2000
DOI: 10.1038/sj.bmt.1702634
|View full text |Cite
|
Sign up to set email alerts
|

Stromal cell-dependent ex vivo expansion of human cord blood progenitors and augmentation of transplantable stem cell activity

Abstract: Summary:In The remarkable proliferation and cell renewal processes in the human hematopoietic system are believed to be supported by a small population of hematopoietic stem cells. 1,2 A major challenge in stem cell research is the establishment of culture systems that facilitate in vitro maintenance and augmentation of stem cell activity. This is of great impor- tance not only for hematopoietic stem cell transplantation but also for gene therapy. It is also an important step towards cellular and molecular und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…Neither IGFBP-1, IGFBP-2, nor IGFBP-3 had an effect on proliferation or maintenance of a primitive immunophenotype of HPC [39]. Many groups including our group have demonstrated that HSC can not be maintained in conditioned culture medium of feeder layer cells under non-contact conditions [11,47,60]. Although studies of other groups have suggested that primitive function of HPC might also be preserved in a transwell setting [40,61], there is evidence that soluble molecules alone are not enough to maintain long-term repopulating potential.…”
Section: Chemokines and Growth Factorsmentioning
confidence: 99%
“…Neither IGFBP-1, IGFBP-2, nor IGFBP-3 had an effect on proliferation or maintenance of a primitive immunophenotype of HPC [39]. Many groups including our group have demonstrated that HSC can not be maintained in conditioned culture medium of feeder layer cells under non-contact conditions [11,47,60]. Although studies of other groups have suggested that primitive function of HPC might also be preserved in a transwell setting [40,61], there is evidence that soluble molecules alone are not enough to maintain long-term repopulating potential.…”
Section: Chemokines and Growth Factorsmentioning
confidence: 99%
“…[48][49][50][51][52][53] One component of the hematopoietic microenvironment, mesenchymal stem cells (MSCs), can be isolated as plastic adherent cells from a variety of fetal and adult tissues. [54][55][56][57] In addition to providing an alternative (co-culture) strategy for CB expansion, allogeneic MSC coadministration has been shown to promote engraftment of human CD34 þ cells in NOD/SCID mice and fetal sheep, [57][58][59][60][61] and MSCs have been shown to have clinical immunomodulatory activity that may impact on graft-versus-host disease in transplant patients. 59,[62][63][64][65][66][67][68][69] CB-MSC co-culture does not require the isolation of CD34 þ or CD133 þ cells before expansion, minimizing manipulation and loss of HPC.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 The production of CAFC week6 or LTC-initiating cells(IC) in ex vivo expansion cultures has been shown to be indicative for the presence and quantity of in vivo repopulating HSC as measured using the quantitative NOD/SCID xenotransplant model. 3,4,[19][20][21] However, behavior of the LTC-IC populations may only partly overlap with that of the HSC and show distinct characteristics under specific experimental conditions. 16,22 Screening a large number of stromal cell lines using this in vivo model is not practical.…”
Section: Introductionmentioning
confidence: 99%